Growth of Streptococcus mutans in Biofilms Alters Peptide Signaling at the Sub-population Level - Shields, Robert C.; Burne, Robert A. (Frontiers in Microbiology, 2016)
Streptococcus mutans activates multiple cellular processes in response to the formation of a complex between comX-inducing peptide (XIP) and the ComR transcriptional regulator. Bulk phase and microfluidic experiments previously revealed that ComR-dependent activation of comX is altered by pH and by carbohydrate source. Biofilm formation is a major factor in bacterial survival and virulence in the oral cavity. Here, we sought to determine the response of S. mutans biofilm cells to XIP during different stages of biofilm maturation. Using flow cytometry and confocal microscopy, we showed that exogenous addition of XIP to early biofilms resulted in robust comX activation. However, as the biofilms matured, increasing amounts of XIP were required to activate comX expression. Single-cell analysis demonstrated that the entire population was responding to XIP with activation of comX in early biofilms, but only a sub-population was responding in mature biofilms. The sub-population response of mature biofilms was retained when the cells were dispersed and then treated with XIP. The proportion and intensity of the bi-modal response of mature biofilm cells was altered in mutants lacking the Type II toxins MazF and RelE, or in a strain lacking the (p)ppGpp synthase/hydrolase RelA. Thus, competence signaling is markedly altered in cells growing in mature biofilms, and pathways that control cell death and growth/survival decisions modulate activation of comX expression in these sessile populations.